Dual roles of inflammatory programmed cell death in cancer: insights into pyroptosis and necroptosis - Wang, Shuai; He, Huanhuan; Qu, Lailiang; Shen, Qianhe; Dai, Yihang (Frontiers in Pharmacology, 2024)
Programmed cell death (PCD) is essential for cellular homeostasis and defense against infections, with inflammatory forms like pyroptosis and necroptosis playing significant roles in cancer. Pyroptosis, mediated by caspases and gasdermin proteins, leads to cell lysis and inflammatory cytokine release. It has been implicated in various diseases, including cancer, where it can either suppress tumor growth or promote tumor progression through chronic inflammation. Necroptosis, involving RIPK1, RIPK3, and MLKL, serves as a backup mechanism when apoptosis is inhibited. In cancer, necroptosis can enhance immune responses or contribute to tumor progression. Both pathways have dual roles in cancer, acting as tumor suppressors or promoting a pro-tumorigenic environment depending on the context. This review explores the molecular mechanisms of pyroptosis and necroptosis, their roles in different cancers, and their potential as therapeutic targets. Understanding the context-dependent effects of these pathways is crucial for developing effective cancer therapies.